Selection of Phalaenopsis amabilis L. Blume Orchid Resistance to Hygromycin - Ixora Sartika Mercuriani; Aziz Purwantoro; Sukarti Moeljopawiro; Seonghoe Jang; Endang Semiarti (Universitas Gadjah Mada, 2012)
Examination of Phalaenopsis amabilis orchid resistance to hygromycin antibiotic is an important step to doprior to Agrobacterium-mediated genetic transformation in this orchids using Hygromycin phosphotransferase(HPT) gene as a selection marker in the T-DNA that harboring a desired gene to be transfered. We exposedthe plant on hygromycin containing medium. The experiment was conducted using 6 weeks old P. amabilisprotocorms. These protocorms were subcultured onto NP medium supplemented with various concentrationof Hygromycin (0, 5, 10, 20, 1nd 40 mg/l). The number of survival protocorms were examined every week for4 weeks after subcultured (WAS). The resistancy of hygromycin was calculated as ratio of death protocormsper total protocorms). The result showed that 10 mg/l hygromycin with 1 weeks of application caused deathclose to LD 50. This data indicate that P. amabilis resistance to hygromycin treatment on the appropriateconcentration 10 mg/l, and this concentration can be used for other purposes in orchid system.